2020
DOI: 10.1109/access.2020.2977663
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level DC/DC Converter for E-Mobility Charging Stations

Abstract: The interest in electric-powered transportation has been increased because of problems such as depletion of fossil fuel resources and environmental issues caused by internal combustion engines. The market for various kinds of small E-mobility devices (EMDs), such as electric vehicles (EVs), E-bikes, segways, and mini-boards has been growing rapidly. Of these, the distribution of the small electric vehicles called personal mobility devices (PMDs), which can address problems such as traffic issues and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…12 (a) shows the simulation results of additional voltage ripple of load voltage waveforms for various dead-time. It is shown that as the dead-time increases, the additional voltage ripple increases as shown in (9). According to the analysis regarding charge sharing loss, the smaller the dead-time or the larger the load capacitor, the smaller the corresponding loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 (a) shows the simulation results of additional voltage ripple of load voltage waveforms for various dead-time. It is shown that as the dead-time increases, the additional voltage ripple increases as shown in (9). According to the analysis regarding charge sharing loss, the smaller the dead-time or the larger the load capacitor, the smaller the corresponding loss.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies related to SVD have been done in terms of power converter [6], [8], [20]- [26]. However, if these technologies are not considered thoroughly along with the peripheral circuits required from the system perspective, they Δ due to (9) Δ are incomplete due to limited applications. Therefore, in this study, the peripheral circuit targeting SVD at the system point of view is considered and compared for both methods at the system-level.…”
Section: System Viewmentioning
confidence: 99%
“…Mobility problems are the result of numerous situations, among which the following can be highlighted: deterioration of air quality, mainly in urban areas [2], [3]; deterioration in health and life quality with reference to traffic noise [2]; traffic congestion, with the loss of productive time and its economic repercussion [4], [5], [6]; urban space destined to infrastructure for the circulation and parking of vehicles [4]; limited and expensive parking spaces [2]; long commuting distances that favour the use of the private vehicles; and seasonal concentration of tourism that results in oversized infrastructure. Changes in the transport sector must start in the cities with boosts for e-mobility transport systems powered by renewable electricity [7], [8]. The establishment and operation of e-mobility services and infrastructures for electric vehicles (EV) that focus on the use of internet of things (IoT) solutions in the management of charging stations is currently an important issue [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is little literature on the use of electric scooters (e-scooter) in urban environments as a new element in micro mobility, but there are studies that show the e-scooter's ability to replace the conventional private vehicles in short urban trajectories [6], [13]. Several reasons explain the increase in the number of e-scooters in cities [8]. E-scooters represent a cheap and independent mobility system with easy parking, and can often share lanes initially intended only for bicycles [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation